Это имя...: стихотворения / Ю. В. Друнина - Друнина Юлия Владимировна (Современник, 1984)
Экземпляры: ЧЗ (20160415) / Инвентарный номер: 10047 / Цена: 0.40 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 76 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6